2008
DOI: 10.1037/0735-7044.122.2.358
|View full text |Cite
|
Sign up to set email alerts
|

Real-time dopamine efflux in the nucleus accumbens core during Pavlovian conditioning.

Abstract: To assess the role of dopamine input to the nucleus accumbens core in anticipatory learning, fast-scan cyclic voltammetry was combined with appetitive Pavlovian conditioning. One group of rats (Paired) received 16 tone-food pairings for at least four daily sessions while the control group (Unpaired) received the same number of unpaired tone and food presentations. Both groups showed transient dopamine responses during food presentation throughout training, confirming dopamine involvement in reward processing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 44 publications
(70 reference statements)
1
30
2
Order By: Relevance
“…Consistent with our previous work (Sunsay & Rebec, 2008) as well as that of others (Day et al, 2007; Stuber et al, 2008), we observed DA signals during tone presentations, suggesting that phasic DA activity in the NAc serves as a neurochemical index of the associative strength of a CS. We also found that extinction reduced the amplitude of the DA signal.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with our previous work (Sunsay & Rebec, 2008) as well as that of others (Day et al, 2007; Stuber et al, 2008), we observed DA signals during tone presentations, suggesting that phasic DA activity in the NAc serves as a neurochemical index of the associative strength of a CS. We also found that extinction reduced the amplitude of the DA signal.…”
Section: Discussionsupporting
confidence: 92%
“…Note the marked decrease in DA amplitude during extinction relative to the other phases. Peak height was measured as percent increase from the inflection point, which is at least two standard deviations above the mean of the preceding three successive points (Sunsay & Rebec, 2008). A repeated-measures ANOVA revealed a significant effect of phase (i.e., acquisition, extinction, reinstatement), F (2, 4) = 8.68, d = 0.9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stabilization of new strategies may be enabled by D 1 receptormediated increases in cortico-striatal synaptic strengths (Floresco et al, 2001;Schotanus and Chergui, 2008) that could occur over the course of new learning during the setshift. Changes in phasic DA signaling may also contribute to the effects of D 1 receptor activation in facilitating setshifting, given that reward-related stimuli promote DA transients in the NAc (Day et al, 2007;Sunsay and Rebec, 2008). However, phasic DA activity in the ventral striatum is thought to act primarily on receptors located in or around DA synapses, whereas increases in tonic DA are believed to affect extrasynaptic receptors (Floresco, 2007).…”
Section: A Selective Role For Nac D 1 Receptors In Strategy Set-shiftingmentioning
confidence: 99%